Changes of main organic acids during vinification. - K. ŠTEFECOVÁ; J. ČEPIČKA (Kvasný průmysl, 2001)
In climate conditions of Czech and Moravian wine region there is usually higher content of lower organic acids than in the regions situated sounthing. Content of tartaric acid is the highest in the grapes, during vinification continuously decrease. Malic acid is oxidated during fermentation, then is degradated by malo-lactic fermentation. Resultant content is very low. Lactic acid doesn't subsist in the grapes, is synthetized during fermentation particularly with bacteria. Succinic acid originate continuously and its content is stable in anaerobial conditions. Quality of acetic acid above 600 mg.l-1 is not desirable, in lower organic acids (citric acid, isocitric acid, ketoglutaric acid) are intermediate products of tricarboxylic cycle and their content is complete wine is low.(In Czech, English summary only)